Policy Analysis for Development and Development of Sports Education: Perspective of Regional Regulation Number 11 of 2017 Concerning the Implementation of Sports - Anshori Nuzul; Yudha Munajat Saputra; Amung Ma’mun; Boyke Mulyana (UNIB Press, 2023)
Regional Regulation Number 11 of 2017 concerning Organizing Sports is the key to the development of sports, especially educational sports. This Regional Regulation places sport as a very important instrument for regional development. However, at this time, sports are still positioned only as the development of the sport itself. So it is not in accordance with what is stated in Regional Regulation Number 11 of 2017. Therefore, the purpose of this study is to find out the Policy for Development and Development of Sports Education from the Perspective of Regional Regulations. The method used in this research is to use a descriptive qualitative approach. Then by making observations, documentation studies, and interviews as a tool for collecting data and for analyzing the data. The results of this study found that the Policy for Development and Development of Sports Education from the Perspective of Regional Regulations was in accordance with Regional Regulation Number 11 of 2017 concerning Organizing Sports. However, there are still deficiencies and inequalities in several aspects such as facilities and infrastructure, the competency of sports teachers who do not yet have competency certificates from the main sports branch and the uneven distribution of schools in implementing special sports class programs.